Emotional self-management in academia - Antoniadou, Marilena; Crowder, Mark (Emerald points., 2021)
Emotional Self-Management in Academia draws on new empirical research from academics' own personal accounts of emotional experiences from their everyday practice to illustrate how their emotional work is adapting in response to a constantly changing workplace. Marilena Antoniadou and Mark Crowder re-examine Hochschild's notion of emotional labour and combine it with emotion regulation strategies and emotional boundaries as utilised into the everyday practices of modern academics. Using illuminating accounts from academics working in the UK, US, Australia, Denmark, Greece and Cyprus, Emotional Self-Management in Academia emphasises that it is emotion - complex, messy and opaque - that drives academics' self-management, as shaped by contextual factors, such as organisational climate. Aimed at academic researchers and professionals, the chapters establish the context of contemporary emotion work and examine it specifically in higher education settings. This is a timely and engaging exploration of the emotional labour of academics today, set against a backdrop of managerial challenges and economic pressures of working in this sector.